2015
DOI: 10.1007/s11126-015-9366-2
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Breastfeeding Exposure and Duration, Neuropsychological Deficits, and Psychopathic Personality Traits in Offspring: The Moderating Role of 5HTTLPR

Abstract: A wealth of research has revealed that a shorter duration of breastfeeding during infancy can increase the risk of various maladaptive traits, including neuropsychological deficits. Despite the number of studies that have been conducted on the topic, few studies have explored whether the effects of breastfeeding on neuropsychological functioning and personality features persist into adulthood. Furthermore, very little research to date has examined whether this relationship is moderated by specific indicators o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 76 publications
0
10
0
Order By: Relevance
“…Supporting the view that there is a neural basis to self-control, multiple studies report a positive association between neuropsychological deficits and low self-control (e.g., Cauffman et al, 2005; Jackson & Beaver, 2013; Ratchford & Beaver, 2009). Related strands of research also provide evidence that neuropsychological deficits are associated with broad measures of antisocial behavior (e.g., Beaver et al, 2012; Jackson, 2017; Jackson & Beaver, 2016; Jackson & Newsome, 2016; Vaske, Newsome, & Boisvert, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Supporting the view that there is a neural basis to self-control, multiple studies report a positive association between neuropsychological deficits and low self-control (e.g., Cauffman et al, 2005; Jackson & Beaver, 2013; Ratchford & Beaver, 2009). Related strands of research also provide evidence that neuropsychological deficits are associated with broad measures of antisocial behavior (e.g., Beaver et al, 2012; Jackson, 2017; Jackson & Beaver, 2016; Jackson & Newsome, 2016; Vaske, Newsome, & Boisvert, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In other words, the roots of psychopathy might be better understood and assessed by looking at a person's early experiences with primary attachment figures. Early experiences of childhood rejection from caregivers could lead to aggression and hostility in adulthood (Leary et al, 2006) and are also likely to shape later life outcomes and psychopathic traits (Bowlby, 1952;Barker et al, 2011;Jackson and Beaver, 2016;Kochanska and Kim, 2013;van der Zouwen et al, 2018). Dutton et al (1996), studying the characteristics of male abusive personality, found that paternal rejection was the strongest predictor of an abusive personality.…”
Section: Identifying Precursors Of Psychopathy: From the Early Beginn...mentioning
confidence: 99%
“…maternal depression, low marital support, socio-economic adversities) significantly increased the odds of a high-stable trajectory of psychopathy or the exacerbation of psychopathic traits across childhood. Jackson and Beaver (2016) analysed data from the National Longitudinal study of Adolescent Health (Add Health) on the potential effect of breast feeding. Add Health was started almost 30 years ago as a large (n = 90,000) US-based prospective longitudinal study.…”
Section: Identifying Precursors Of Psychopathy: From the Early Beginn...mentioning
confidence: 99%
See 1 more Smart Citation
“…A few studies have suggested that factors during infancy predict psychopathic traits in adolescence or adulthood. Using data from the National Longitudinal Study of Adolescent Health (Add Health), Jackson and Beaver () found that no exposure to breast‐feeding during infancy and a shorter duration of breast‐feeding significantly increased the risk for psychopathic personality traits in adulthood (ages 24–32) when controlling for sex, race, and SES. Furthermore, neuropsychological deficits (specifically verbal skills) significantly mediated the relationship between exposure to breast‐feeding and psychopathic personality traits in adulthood.…”
Section: Early Life Factors Predicting Later Psychopathic or Cu Traitmentioning
confidence: 99%